A Molecular Assay to Quantify Male and Female Plasmodium falciparum Gametocytes: Results From 2 Randomized Controlled Trials Using Primaquine for Gametocyte Clearance. (6th July 2017) - Stone, Will; Sawa, Patrick; Lanke, Kjerstin; Rijpma, Sanna; Oriango, Robin; Nyaurah, Maureen; Osodo, Paul; Osoti, Victor; Mahamar, Almahamoudou; Diawara, Halimatou; Woestenenk, Rob; Graumans, Wouter; et al.
Summary: A sensitive molecular assay was developed to quantify male and female Plasmodium falciparum gametocytes. Its application in 2 clinical trials demonstrates that the early effects of primaquine may be due to gametocyte fitness rather than sex ratio. Abstract: Background: Single low-dose primaquine (PQ) reduces Plasmodium falciparum infectivity before it impacts gametocyte density. Here, we examined the effect of PQ on gametocyte sex ratio as a possible explanation for this early sterilizing effect. Methods: Quantitative reverse-transcription polymerase chain reaction assays were developed to quantify female gametocytes (targeting Pfs25 messenger RNA [mRNA]) and male gametocytes (targeting Pf3D7_1469900 mRNA) in 2 randomized trials in Kenya and Mali, comparing dihydroartemisinin-piperaquine (DP) alone to DP with PQ. Gametocyte sex ratio was examined in relation to time since treatment and infectivity to mosquitoes. Results: In Kenya, the median proportion of male gametocytes was 0.33 at baseline. Seven days after treatment, gametocyte density was significantly reduced in the DP-PQ arm relative to the DP arm (females: 0.05% [interquartile range IQR, 0.0–0.7%] of baseline; males: 3.4% [IQR, 0.4%–32.9%] of baseline; P < .001). Twenty-four hours after treatment, gametocyte sex ratio became male-biased and was not significantly different between the DP and DP-PQ groups. In Mali, there was no significant difference in sex ratio between the DP and DP-PQ groups (>0.125 mg/kg) 48 hours after treatment, and gametocyte sex ratio was not associated with mosquito infection rates. Conclusions: The early sterilizing effects of PQ may not be explained by the preferential clearance of male gametocytes and may be due to an effect on gametocyte fitness.